IMPROVING THE METHODOLOGY OF USING INTERACTIVE METHODS IN TEACHING FINE ARTS IN GENERAL SECONDARY SCHOOLS - Temirova Muqaddas Ibrahimjon kizi; Otamirzayeva Mohinur Ilxomjon qizi (Galaxy International Interdisciplinary Research Journal, 2024)
This article is about "Improving the methodology of using interactive methods in the teaching of visual arts in general secondary schools". Fine art helps children to know existence and life. Before starting to draw pictures of things and events, they study the structure, shape, dimensions, color, and spatial conditions of things and depict them in their works. They also get an idea about the life of the observed living things, as a result, children’s imagination about the world deepens, expands, and their memories develop.